The Transfer Problem Revisited : Net Foreign Assets and Real Exchange Rates - Milesi-Ferretti, Gian.; Lane, Philip (Washington, D.C. : International Monetary Fund, 2000)
The relationship between international payments and the real exchange rate-the 'transfer problem'-is a classic question in international economics. We use new data on countries' net external positions together with real exchange rate data to shed light on this question. We present a model yielding testable implications on the long-run co-movements of real exchange rates, external positions, relative GDP and terms of trade, and cross-country and time-series evidence on the subject. Countries with net external liabilities are found to have more depreciated real exchange rates, with the main channel of transmission working through the relative price of nontraded goods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet